Mahagoni (Swietenia spp.) - naravna in kulturna zgodovina - Torelli, Niko (Gozdarski vestnik, 2006)
Described are the systematics of the genus Swietenia and the origin of the name "mahogany". The history of use and characteristic features of mahogany are shown, with an emphasis on figure and dimensional stability. The microscopic structure and the difficulty of positive xylotomic identification are described in more detail. Following the almost complete extinction of Spanish or Cuban mahogany (Swietenia mahagoni Jacq.), Honduras or Mexican mahogany (Swietenia macrophylla King) is also endangered, especially in the northern border of its areal (Central America, Mexico). The Lacandon sustainable use of the rain forest is described, as is end-use grouping of wood species as an alternative to detrimental highly selective felling. Due tothe excellent reputation of mahogany, attempts have been made to unjustifiedly and non-professionally name wood having a similar appearance, such as reddish colour of heartwood, radial ribbon figure due to interlocked grain, etc. Both properties are fairly common in tropical species, therefore the "list of mahoganies" is so long (Table 1). All three species of mahogany are listed in the IUCN Red List and in CITES Appendix II.
Keywords: Swietenia spp.; mahagoni; izvor imena; zgodovina rabe; ohranitev; lesne lastnosti; dimenzijska stabilnost; teksture